THE EFFECT OF TOTAL DEBT AND WORKING CAPITAL ON NET INCOME IN RETAIL TRADING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2021 PERIOD - Ni Made Widya Savitri; Abdi Akbar; Anwar; Muhammad Ichwan Musa; Nurman (Transpublika Publisher, 2023)
The progress and profitability of a company are intricately linked to its financial management, specifically regarding total debt and working capital. This study aims to empirically examine the impact of Total Debt and Working Capital on Net Income in retail trade sub-sector companies listed on the Indonesia Stock Exchange during the period from 2019 to 2021. Employing quantitative research methods, the study employs purposive sampling to gather data. The sample comprises 24 companies. The study considers total debt and working capital as independent variables, while net income serves as the dependent variable. Secondary data is collected from the official website of the Indonesia Stock Exchange and analyzed using multiple linear regression analysis. The findings demonstrate that working capital has a significant partial effect on net income, and both total debt and working capital exhibit a positive and significant simultaneous effect on net income in retail trading companies listed on the IDX between 2019 and 2021.